Parental medical background and pre-admission preparedness in China’s medical student selection - Jin Yang; Hongbin Wu (Medical Education Online, 2025)
Introduction While children of medical professionals are globally overrepresented in medical schools, evidence from China remains limited. This study examines parental medical background prevalence among Chinese medical undergraduates, its association with admission outcomes, and disparities in pre-admission preparedness within China’s meritocratic National College Entrance Examination (NCEE) system – a critical context given its role as the primary gateway to higher education.Methods Using data from the 2021 China Medical Student Survey (CMSS), a nationally representative sample of 19,299 clinical medical students was analyzed. Linear and logistic regression models were employed to assess the relationship between parental medical background and admission outcomes/pre-admission preparedness, controlling for socio-demographic covariates (e.g. gender, urban/rural residency, family income) and institutional/provincial fixed effects.Results Children of medical professionals were significantly overrepresented (11.60% vs. 0.34% national physician-population ratio). Parental medical background did not predict advantages in NCEE scores or admission to long-term programs. However, paternal medical background was associated with higher pre-admission preparedness in clinical practice (β = 0.199, p < 0.05), health and society (β = 0.205, p < 0.01), professionalism (β = 0.130, p < 0.05), and a greater likelihood of understanding the major (OR = 0.724, p < 0.01), while maternal background only correlated with understanding of the major (OR = 0.623, p < 0.01)Conclusions In the context of China’s NCEE-based student selection system, parental medical background has no direct influence on admission results, yet intergenerational disparities in preparedness persist. To foster substantive equity, China’s meritocratic system could integrate targeted interventions (e.g. pre-med mentorship for disadvantaged students). These findings underscore the global imperative to balance meritocracy with policies addressing structural inequities in medical student selection.